ANALYSIS OF CAPABILITY GAP IN COVERING VACANT POSITION OF D&C OPERATION PT. SOG - Wilan, Utari
The impact of the IBU-T implementation has made some lines in the organization lost talent in critical roles including DWSM position in Drilling and Completion (D&C). Alternatively, those positions are filled by consultants from the business partner that tied under contracts with D&C. The ratio of consultant involvement is getting higher since existing employee of PT. SOG reached retirement age, from 10% to 20% at the end of 2018 and predicted rise to 35% at the end of 2019. The management began to concern on consultant role due to getting complaint from the team leader (consultant direct user) prior most incidents occurred when a site was supervised by consultant. This research aims to help D&C to evaluate DWSM consultant role that currently substitute employee in operation. This research will first figure out non-satisfaction aspect of consultants in D&C, identify gap between current and expectation, and recommend how the organization should fulfill the gap. Using 5 Whys to gain better understanding regarding the root cause of the problem, recommend the team to identify capability that required for DWSM vacant position. Capability Based Assessment (CBA) is conducted to address un-ideal condition of current consultant performance toward D&C expectation. Started with initial preparation to define SME involved and obtain list of position’s capabilities, CBA followed by assessment of current capability condition. After identification of current capability level, it is compared to expected capability level to have gap analysis. Each capability gap will be categorized based on its “level of value” provided. This value level becomes a basis to generate HCM value chain and lead to the “input” for what the team really needs to do to fill the gaps. Finally, this research found the non-satisfaction aspect is in consultant capability. It has been identified that there are 12 capability gaps between current Consultant and expectation. By having these gaps, it means D&C currently facing lack of capable personnel for the position. Using HCM Value Matrix, is it generated that the D&C Operation needs conduct recruitment of new employee to enable the team implements 5 discipline of “the learning organization” to get the talent into expected capability level.